Pengaruh Perilaku Body Shaming terhadap Tingkat Kepercayaan Diri pada Mahasiswa Psikologi di Universitas - Aldila Dyas Nurfitri; Anindita Retya Putri; Astriana Khikmawati; Muhammad Akmal Rafli; Zulfa Fahmy (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Body shaming has emerged as a prevalent phenomenon, particularly among student populations. It involves the act of insulting individuals based on their perceived physical differences. This detrimental behavior significantly impacts one's self-confidence. The present study aims to investigate the influence of body shaming on the self-confidence levels of students at UIN Walisongo Semarang. The research specifically focuses on students enrolled in the psychology study program at UIN Walisongo Semarang. The research methodology employed the scale method and utilized random sampling for data collection. The findings of this study reveal a significant relationship between body-shaming behavior and self-confidence levels among students at UIN Walisongo Semarang. The statistical analysis yielded a significance value of 0.000 < 0.05, indicating that the body shaming variable (X) indeed affects the self-confidence variable (Y).